Avances y resistencias del profesorado ante el uso de los Smart Mobile Devices (SMDs) y los Social Network Sites (SNS) - Gutiérrez-Ortega, Mónica; García Tamarit, Consuelo; Fandos Igado, Manuel (Education in the Knowledge Society (EKS), 2021)
Los dispositivos móviles inteligentes (SMD) y las redes sociales (SNS) han sido responsables de introducir amplias innovaciones en el campo de la educación. Las percepciones de los docentes sobre la utilidad educativa de los SMD y los SNS pueden ser un facilitador o una barrera para su uso en las aulas. La presente investigación pretende conocer, a través de un estudio predictivo, la utilidad percibida sobre los SMD y los SNS de los docentes españoles y analizar la influencia de las variables demográficas (edad, género y nivel educativo) sobre ella. La muestra comprende 2,659 profesores de toda España de niveles educativos no universitarios. Para la recogida de datos se ha empleado un cuestionario ad hoc previamente validado. Los resultados apuntan a que las variables sociodemográficas, la disponibilidad de recursos tecnológicos y la presencia en redes sociales pueden predecir la percepción del profesorado sobre su utilidad para los procesos de enseñanza-aprendizaje.
Progress and Resistance of Teachers at the Use of Smart Mobile Devices (SMD) and Social Network Sites (SNS)
Smart mobile devices (SMD) and social networks (SNS) have been responsible for introducing extensive innovations in society and in education as well, though with greater difficulties. In fact, the teacher's perception of the educational utility of SMD and SNS can be a facilitator or a barrier for their use in the classroom. This research tries to find out, through a predictive study, the perceived usefulness of SMD and SNS by Spanish teachers and to analyse the influence of demographic variables (age, gender and educational level) on it. The group of study were 2,659 non-university teachers from all over Spain. For data collection, the Questionnaire on the Utility of Social Networks and the Smartphone for Educational Action (CURSAE) has been used. Results show that certain socio-demographic variables, availability of technological resources and presence in social networks can predict teachers' perception of the educational utility of SMD and SNS. These results are expected to provide support to those institutions in charge of teachers' professional development in Spain, since they offer information on certain factors that may be influencing the acceptance or resistance of teachers to integrate SMD and SNS in the classrooms and in academic life.
Keywords: utilidad; profesorado; percepción; dispositivos móviles; redes sociales; usefulness; teachers; perception; smart mobile devices; social network sites; Emerging